Evaluating soil physico-chemical properties and nutrient availability through intensified conservation agriculture-based cropping systems - Kumar, Arun; Saini, Kulvir Singh; Sharma, Sandeep; Yadav, Manish; Singh, Gurjeet; Devi, Kavita; Kumawat, Kailash Chand (Frontiers in Agronomy, 2025)
Conservation agriculture (CA) practices have been widely promoted and recognized for their potential to enhance soil sustainability by improving soil properties. The purpose of the 2-year field experiment was to investigate the effect of diversified CA -based cropping systems on nutrient availability and soil characteristics. The study was conducted using a randomized complete block design (RCBD) with four replications at each site. Six cropping system (CS) scenarios were tested: S1—rice–wheat–mungbean (R-W-SM) under conventional tillage (CT) without residue retention (R0); S2—R-W-SM under CA with residue retention (R+); S3—maize–wheat–mungbean (M-W-SM) under CT (R0); S4—M-W-SM under permanent bed (PB) with R+; S5—soybean–wheat- mungbean (S-W-SM) under CT (R0); and S6—S-W-SM under PB with R +. Though each annual cropping cycle spanned 1 year, the inclusion of mungbean (summer mungbean) in the same year allowed the assessment of a three-crop rotation within each year. After two cropping years (effectively covering two complete crop rotation cycles), the results indicated that S6 significantly improved the soil properties: bulk density decreased by 4.4% and infiltration rate increased by 45.6% compared with S1. Soil organic carbon and macro- and micro-nutrient availability were notably higher under CA-based systems (S2, S4, and S6). The highest microbial biomass, enzymatic activity, and basal soil respiration (BSR) were recorded in S6. In both years, dehydrogenase activity (DHA) and BSR increased by 58.5%–64.6% under S6 compared with 40.7%–41.4% in S1. Micro-nutrients like Zn, Fe, Mn, and Cu were improved by 10%, 39%, 8%, and 63%, respectively, in S6 over S1. These findings suggest that CA-based soybean–wheat –mungbean systems (S6) can substantially enhance soil health and nutrient dynamics in a short-term rotation and may guide future sustainable agriculture.